Dynamic vibration extinguished on a viscously elastic base - Kulmuratov, Nurillo Raximovich; Ishmamatov, Matlab Raxmatovich; Xalilov, Shaxob Fayzievich; Akhmedov, N.B. (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the work is to develop algorithms and a set of programs for studying the dynamic characteristics of viscoelastic thin plates on a deformable base on which it is installed with several dynamic dampers. The theory of thin plates is used to obtain the equation of motion for the plate. The relationship between the efforts and the stirred plate obeys in the hereditary Boltzmann Voltaire integral.
Keywords: dynamic dampers; oscillations; viscoelastic plate; integro-differential equations; amplitude-frequency dependence; Boltzmann-Voltaire integral